Bellboy Work Motivation: Studying at a Star Hotel in Bali - Pynatih, Putu Deny Mahendra; Indrayani, I Gusti Ayu Putu Wita; Iswarini, Ni Ketut (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to determine the work motivation of bellboys at Hotel ABC Bali. Data collection was carried out by distributing questionnaires to bellboy staff, then confirmed through interviews with bell captains to confirm the results of the questionnaire and to conduct documentation as supporting evidence. The data analysis technique used in this study is a qualitative descriptive method. This study refers to the two-factor work motivation theory according to Fredrick Herzberg. The results of the analysis showed that the motivation of bellboy staff was 3.34 with a fairly satisfied predicate. As for the intrinsic or hygienic factor, it has the highest level of satisfaction, namely 3.57 with a satisfied predicate, while the extrinsic or motivation factor gets the lowest value, namely 3.11 with a fairly satisfied predicate.